Mempersiapkan Pendidikan di Era Tren Digital (Society 5.0) - Kisah Irawan Mega (Nusa Putra University, 2022)
Education in the Revolutionary Era 5.0 has transformed through various changes, one of which is the education system is required to be adapted to the demands of the 5.0 revolution era. The purpose of this research is to prepare and find out the methods that are prepared to welcome the new revolution era in the perspective of the world of education. This research uses qualitative research with a literature study approach. Sources of data in this study are journals, articles, books and other relevant references. Data collection techniques were carried out by literature study and documentation. The results show that in the world of information technology education, digital trends cannot be avoided and have a very large impact, therefore to realize education in accordance with the times, education, especially in Indonesia, must be ready to face digital trends by equipping students, making people aware of developments. information technology in order to compete with other countries. The presence of the 5.0 revolution era will open up the world of students' horizons that learning resources are not only available in school but can be obtained outside of school.